Pengaruh Pembiayaan Murabahah, Mudharabah, Dan Musyarakah Terhadap Profitabilitas - Syaiful Bahri (LPPM ISNJ Bengkalis, 2022)
This research aimed to show the effect of murabahah, mudharabah, and musyarakah financing on the profitability of Islamic commercial banks. The research is a causal associative with a quantitative approach. The research population is Islamic commercial banks in Indonesia. The sampling technique used non-probability sampling with a purposive sampling method and obtained nine samples. The data analysis technique used descriptive analysis, classical assumption test, multiple linear regressions, coefficient of determination test, and t-test. The results showed that murabahah financing did not affect profitability. However, mudharabah financing has a positive effect on profitability. Meanwhile, musyarakah financing has a significant negative impact on profitability. This research can be a reference for banks to increase murabahah and musyarakah financing so that profitability can increase adequately. Then it can be a reference for the bank to be more selective if there is a suspension of payments on murabahah financing.